Civic Disposition in Communities from Riverbanks to Barito Kuala Regency - Wahyu Wahyu; Mariatul Kiptiah (Asean Study Center Lambung Mangkurat University, 2022)
For the people on the banks of the Barito Kuala area, the river is not only a source of water but also a self-identity and life orientation. The Barito Kulada people are an indigenous tribe from South Kalimantan. The people who live in Barito Kuala Regency are a group of people originating from Banjar Kuala in South Kalimantan but bordering Kapuas in Central Kalimantan. Development occurred in Barito-Kuala Regency, an area of a thousand rivers with traditional settlements located on the banks of the river with buildings facing the river. Currently, many community houses are along the river banks facing the river. This study aims to examine and seek natural phenomena and cultural heritage of local wisdom in building the existence of civic disposition in riverbank communities to maintain democratic values and responsibility based on residents. This study uses a qualitative approach through descriptive research methods: direct observation, interviews, documentation, and debriefing of work completed in the field. The results of this study show the following: Citizenship in riverbank communities in Barito-Kuala Regency under the currents of globalization leads to a lifestyle of the younger generation that continues to preserve local wisdom with positive behavior in riverbank communities, supports the existence of citizenship towards nature and the environment, which the source can be in the form of community values, customs, ancestral advice or local wisdom, a culture that is formed naturally and continues to exist in society to adapt to the environment. The riverbank community in Barito Kuala Regency is aware of the responsibilities, actions taken, and moral obligations as a democratic society, as well as the welfare implications of the care and maintenance of the riverbanks by the riverbank community.